Analysis regarding Physical Activity and Health Among Romanian Students from University of Oradea - Dana Ioana CRISTEA; Anca-Cristina POP; Aurelian Andrei CRISTEA; Ilie Madalin ABRAHAM; Mirela STEF (Romanian Journal of Physical Therapy)
Introduction: Health is a whole consisting of physical, mental and last but not least social well-being. In this work, we proposed to analyze the frequency of participation of students from the University of Oradea in physical activities during their free time. Materials and Methods: We conducted a survey by distributing a questionnaire, consisting of 11 questions, to 195 students from the University of Oradea, from different specializations, aged between 18-30 years. Results: Regarding the frequency of practicing physical activities among students based the data obtained after the distribution of the survey, we concluded the following: 60% of the students from the University of Oradea consider themselves to be active people in their everyday life, 32% of them consider that they lead a sedentary life. 81% of Romanian students believe that physical activity is important, while 8% believe that physical activity is not important; 55% of students prefer other activities than sports, and only 35% prefer sports; there are differences between the frequency of participation in physical activities according to the amount that is invested in this type of activity. Conclusion: We can say that as the amount invested increases, the frequency of practicing sports activities is higher.